INFLUENCE OF THE GREEN ECONOMY AND SOCIAL RESPONSIBILITY ON ENVIRONMENTAL SUSTAINABILITY: AN EXPLANATORY ANALYSIS IN THE PERUVIAN AGRICULTURAL SECTOR - Chacón Gutiérrez, Dennis; Robles Fabián, Daniel Amadeo; Pedroza San Miguel, Rosa Diana; Silvera Arcos, Susan Madeleine; Calderon Pizango, Milton Ricardo; Espinoza Paucar, Oscar Nestor (LACCEI, 2025)
Abstract– The purpose of this article was to find the influence of the practices of the green economy and social responsibility on environmental sustainability, its research method was quantitative, non-experimental, explanatory and transversal, its population was 125 workers from Agrícola Cerro Prieto, a probabilistic sample of 77 participants was taken to carry out the survey using 3 questionnaires on a Likert scale, validated and reliable. The results when applying multiple linear regression showed a Sig. 1,96 confirming that the predictor variables do influence the dependent variable applied to the study unit. It is concluded that the green economy and social responsibility have a positive impact on the environmental sustainability of the agricultural sector in Peru, however, their incorporation is restricted, requiring comprehensive policies that eliminate the differences between discourse and action for an authentic effect. Keywords: Green economy, social responsibility, environmental sustainability, agricultural sector.